A boy like you - Murphy, Frank 1966- (Sleeping Bear Press, 2019)
Encourages every boy to embrace all of the things that make him unique, and to be curious, brave, kind, thoughtful, and more.
Keywords: Männlichkeit; Junge; Bilderbuch; Rollenbilder; Authentizität; Geschlechterrollen; Erzählerische Bilderbücher; Kinderbuch